Rapid Genome-Wide Location-Specific Polymorphic SSR Marker Discovery in Black Pepper by GBS Approach - Negi, Ankita; Singh, Kalpana; Jaiswal, Sarika; Kokkat, Johnson George; Angadi, Ulavappa B.; Iquebal, Mir Asif; Umadevi, P.; Rai, Anil; Kumar, Dinesh (Frontiers in Plant Science, 2022)
Black pepper (Piper nigrum), the “King of Spices”, is an economically important spice in India and known for medicinal and cultural values. SSRs, the tandem repeats of small DNA sequences are often polymorphic in nature with diverse applications. For population structure, QTL/gene discovery, MAS and diversity analysis, it is imperative to have their location specificity. The existing PinigSSRdb catalogues approximately 70K putative SSR markers but these are anonymous (unknown chromosomal location), based on 916 scaffolds rather than 26 chromosomes. Under this study, we generated ddRAD sequence data of 29 black pepper genotypes from all over India, being low cost and most efficient technique for identification of polymorphic markers. The major limitation of ddRAD with compromised/ non-uniform coverage has been successfully overcome by taking advantage of chromosome-wise data availability. The latest black pepper genome assembly was used to extract genome-wide SSRs. A total of 276230 genomic SSRs were mined distributed over 26 chromosomes, with relative density 362.88 SSRs/Mb and average distance 2.76 Kb between two SSRs. This assembly was also used to find the polymorphic SSRs in the generated GBS data of 29 black pepper genotypes utilizing rapid and cost-effective method giving 3176 polymorphic SSRs, out of which 2015 were found to be hypervariable. The developed web genomic-resource, BlackP2MSATdb (http://webtom.cabgrid.res.in/blackp2msatdb/) is the largest and first reported web-resource for genomic and polymorphic SSRs of black pepper, which is useful to develop variety signature, coreset, physical map, QTL/gene identification and MAS in endeavour of black pepper production.